The rSPA Processes of River Water-quality Analysis System for Critical Contaminate Detection, Classification Multiple-water-quality-parameter Values and Real-time Notification - VEESOMMAI, Chalisa; KIYOKI, Yasushi (Politeknik Elektronika Negeri Surabaya (PENS), 2016)
The water quality analysis is one of the most important aspects of designing environmental systems. It is necessary to realize detection and classification processes and systems for water quality analysis. The important direction is to lead to uncomplicated understanding for public utilization. This paper presents the river Sensing Processing Actuation processes (rSPA) for determination and classification of multiple-water- parameters in Chaophraya river. According to rSPA processes of multiple-water-quality-parameters, we find the pollutants of conductivity, salinity and total dissolved solid (TDS), which are accumulated from upstream to downstream. In several spots of the river, we have analyzed water quality in a maximum value of pollutants in term of oxidation-reduction potential (ORP). The first range effect of parameter is to express high to very high effects in term of dissolved oxygen, second is to express intermediate to very high effect in term of conductivity, third is to express low to very high effect in term of total dissolved solid, fourth is to express completely safe to very high effect in term of turbidity and the final is to express completely safe for effect in term of salinity.